2016
DOI: 10.3389/fpsyg.2016.01682
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress-Related Factors, and Blood Pressure in Young Adults

Abstract: Hypertension (HT) is a long-term medical condition characterized by persistently elevated blood pressure (BP) in the arterial vessels. Although HT initially is an asymptomatic condition, it chronically evolves into a major risk factor for cardiovascular, cerebrovascular, and renal diseases that, in turn, represent crucial causes of morbidity and mortality in industrialized countries. HT is a complex disorder that is estimated to affect more than a quarter of the world’s adult population. It is classified on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 108 publications
4
57
1
7
Order By: Relevance
“…We found a positive correlation between the blood pressure relative to the baseline and the emotion self-report. This finding agree with (Mucci et al 2016) that showed a positive correlation between anxiety and blood pressure. Based on the blood pressure, anxious participants had a higher rate than non-anxious.…”
Section: Question 2: Identifying Fla Using Physical Instrumentssupporting
confidence: 93%
See 3 more Smart Citations
“…We found a positive correlation between the blood pressure relative to the baseline and the emotion self-report. This finding agree with (Mucci et al 2016) that showed a positive correlation between anxiety and blood pressure. Based on the blood pressure, anxious participants had a higher rate than non-anxious.…”
Section: Question 2: Identifying Fla Using Physical Instrumentssupporting
confidence: 93%
“…Similar to (Mucci et al 2016;Zhang et al 2011), the blood pressure was higher for anxious learners than non-anxious learners. Although both median and average reading for both groups were in the normal range according to (Whelton et al 2018), there was a slight increase in the average blood pressure reading for anxious learners.…”
Section: Question 1: the Relationship Between Classroom Anxiety And Imentioning
confidence: 81%
See 2 more Smart Citations
“…The adaptation of work to an individual's skills should be a continuous and dynamic process and should not be a particular problem for production activities with an appropriate risk assessment [12]. In particular, risk assessment policies should be oriented to all workers, regardless of age, feel motivated to pursue their goals and those of the company [13,14]. An innovative approach is to examine the psychological processes and healthy habits involved in the motivation and interaction with the company system [15 -17].…”
Section: Active Aging: Definition and Lawsmentioning
confidence: 99%